MAXIMIZING MILLENNIAL JOB SATISFACTION: THE KEY ROLES OF MEANINGFUL WORK AND RESILIENCE - Muchtadin, Muchtadin (Biopsikososial: Jurnal Ilmiah Psikologi Fakultas Psikologi Universitas Mercubuana Jakarta, 2024)
The millennial generation has different characteristics from previous generations. It is important for organizations to know the characteristics of millennials because they can bring advantages and disadvantages to the organization. This research aims to determine the magnitude of the influence of learning agility, meaningful work, and resilience on job satisfaction of the millennial generation. A quantitative causality design was applied in this research. Respondents were 100 millennial workers in Indonesia. Research data was taken via Google Form via Facebook, WhatsApp and Linked-in. Data analysis was carried out using the PLS SEM method. The research results show that learning agility has no effect on millennial job satisfaction. Meaningful work has a significant positive effect on millennial job satisfaction. Resilience has a significant positive effect on millennial job satisfaction. Future research can limit respondents to one sector, such as private and public. Future researchers can use the mediation of meaningful work and resilience on the influence of learning agility on job satisfaction. This research contributes to efforts to increase job satisfaction of the millennial generation through learning agility, meaningful work and resilience.